Separating Abram and Lot: the narrative role and early reception of Genesis 13 - Rickett, Dan (Themes in biblical narrative, 2019)
Intro -- Contents -- Preface -- Abbreviations -- Introduction -- 1 The Methodology of the Present Volume -- 2 The Literary Function of Genesis 13 in Modern Scholarly Discussion -- 3 Understanding the Separation of Abram and Lot -- 4 The Thesis of the Present Volume -- 1 Abram's Problematic Taking of Lot and the Beginnings of Separation -- 1 Defining What Abram Is Called to Leave -- 2 Reading Lot as Abram's Potential Heir -- 3 Lot as a Member of Terah's Household -- 4 Abram's Return to the Land -- 5 Abram's Worship and Abram and Lot's Property -- 6 Concluding Remarks -- 2 Brotherhood, Separation and Settlement -- 1 A Burdened Land and Striving Herders -- 2 Abram's (Problematic) Offer -- 3 Lot Sees and Chooses the Plain of the Jordan -- 4 The Brothers Separate and SettleThe settlement of Abram in Canaan and Lot -- 5 Lot's Choice and the People of Sodom -- 6 God's Promises to Abram in Light of Lot's Departure -- 7 Lot Is Not a Descendant -- 8 Abram in Yhwh's Space -- 9 Concluding Remarks -- 10 Moving Toward Reception -- 3 Solving Abram's Problems: Reception of Genesis 13 in LXX, Jubilees and Genesis Apocryphon -- 1 Introductory Comments on Ancient Interpretation of Genesis 13 -- 2 Genesis 13 in the Earliest Scriptural Retellings -- 3 Conclusion -- 4 Creating an Unrighteous Outsider: Later Jewish Reception of Genesis 13 -- 1 Philo -- 2 Josephus -- 3 The Targums -- 4 Midrashic Literature -- 5 Two Stories of Separation-Lot and Ruth -- 6 Concluding Thoughts -- 5 Lot as In-between: Early Christian Reception of Genesis 13 -- 1 Julius Africanus -- 2 Origen -- 3 Ephrem -- 4 Jerome -- 5 Ambrose -- 6 Chrysostom -- 7 Augustine -- 8 Early Christian Art -- 9 Concluding Remarks on Christian Interpretation -- 10 The Separation of Abram and Lot in Later Medieval and Renaissance Reception -- 11 Moving toward an Interpretation -- 6 Lot as Brother.